2017
DOI: 10.3390/ma10030244
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behavior of Ceramic CAD/CAM Crowns and Natural Antagonists

Abstract: Objective: Evaluation of wear behavior of computer-aided design/computer-aided manufacturing (CAD/CAM) crowns from various restorative materials and natural antagonists. Method: Full CAD/CAM crowns fabricated with nanoceramic resin (Lava Ultimate (LU)), a glass ceramic in a resin interpenetrating matrix (Vita Enamic (VE)) and a lithium silicate reinforced ceramic enriched with zirconia (Vita Suprinity (VS)) were cemented on human molars. The crown and antagonists were subjected to simulated chewing. 3D data se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…When the effects of storage media on wear were examined, the present study found none of the tested materials to show any significant differences in two‐body wear rates following storage in different media. Because previous studies evaluating wear resistance and other mechanical properties of resin‐matrix ceramic materials were conducted with only one type of storage media, no comparisons can be made regarding the effects of different storage media on the wear of resin‐matrix ceramics. While both Lava Ultimate and Paradigm MZ100 have been shown to be susceptible to roughening under acidic conditions due to the hydrolysis of the methacrylate ester bonds in their polymer matrixes, whether there is a direct correlation between the surface roughness and wear rates of these materials has yet to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…When the effects of storage media on wear were examined, the present study found none of the tested materials to show any significant differences in two‐body wear rates following storage in different media. Because previous studies evaluating wear resistance and other mechanical properties of resin‐matrix ceramic materials were conducted with only one type of storage media, no comparisons can be made regarding the effects of different storage media on the wear of resin‐matrix ceramics. While both Lava Ultimate and Paradigm MZ100 have been shown to be susceptible to roughening under acidic conditions due to the hydrolysis of the methacrylate ester bonds in their polymer matrixes, whether there is a direct correlation between the surface roughness and wear rates of these materials has yet to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…1A) and superimposed ( Fig. 1B) from the baseline using a 3D digital parametric inspection software (GOM Inspect, Braunschweig, Germany) (9). This software generated a colorimetric map of each specimen and then aligned the models to detect the geometric changes that illustrate the wear caused by the antagonist (Fig.…”
Section: Parametric Wear and Volume Loss Analysismentioning
confidence: 99%
“…A methodology that simulates a longitudinal evaluation is the wear resistance of restorative materials (9,10). A material with good resistance to wear will not modify the patient's vertical dimension, nor the restoration shape and its consequent aesthetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental wear is a complex process that results in irregular loading on the occlusal surface, loss of the tooth surface substance, and changes in masticatory functions. Many factors influence the surface roughness and wear of the restorative materials and the antagonist tooth, including the quality of the finishing and the polishing or glazing of the occlusal surface of the dental ceramic [5]. Finishing and polishing techniques have been identified that create surfaces comparable to or better than those of glazed porcelain [14].…”
mentioning
confidence: 99%